Exploring Professional Competencies for Talent Management in Hospitality and Food Sector in Turkey - Sabuncu, Kerem U.; Karacay, Gaye (Elsevier BV, 2016)
Abstract This study is an exploratory research conducted for understanding talent management practices in hospitality and food sector in Turkish business environment. The data of the study was collected via face-to-face interviews from employees working in the small and medium sized companies in Turkish hospitality and food sector. The data obtained through in-depth interviews was analyzed by content analysis. The main aim of the current study is identifying strategic talent attributes in Turkish hospitality and food sector through a qualitative research. The outcomes of the current study will be utilized as the groundwork of a further quantitative research in order to construct a professional competence scale for hospitality and food sector in Turkish business environment.